STRES KERJA DAN KONFLIK KERJA PENGARUHNYA TERHADAP KINERJA KARYAWAN - Krisnawati, Siti; Lestari, Yuyun Tri (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
The purpose of this paper is to examine the relationship between stress, conflict and job performance. Data were collected from 40 employees using anonymously completed questionnaires. The results indicate that work stress and conflict have a negative and significant influence on employee performance. Thus, the higher the stress and perceived conflict, the lower the employee's performance. This research can provide useful input to help companies take appropriate steps to improve employee performance by overcoming stress and work conflicts that occur within the company. Keywords: work stress, conflict, performance